Opportunities and Challenges of the DPW Crescent Star Party in Elections in North Sumatra - Efendi Samosir, Hasrat (Budapest International Research and Critics University, 2018)
In the context of Indonesia where the population is predominantly Muslim (even the largest Muslim country in the world) the views above are very relevant if linked to the political life of Muslims. In the 2009 General Election the UN vote was greatly reduced and could not exceed the 2.5% threshold, so that they could not place their representatives in the DPR RI, in connection with that the UN DPP through the Independent Survey Institute of the University of Indonesia (UI) had done survey to find out the causes, with results: first, the Candidate Figure is unknown or unpopular. Second, party administrators are less well known and not close to the community. Third, programs and issues are not in accordance with the aspirations of the people. Fourth, the image of leaders and administrators is rarely covered by the mass media. Fifth, the performance of legislators and regional heads from the United Nations is not aspiration and less publicized.